THE IMPACT OF LEADERSHIP STYLE, ORGANIZATIONAL CULTURE, AND MOTIVATION ON PERSONNEL PERFORMANCE AT THE INDONESIAN NAVY SUPPLY CENTER DEPOT - Tatan Sukwika; Hisar Panjaitan; Yohanes Sulistyadi; Nugroho Budisatrio Sukamdani; Hariyadi Budisantoso Sukamdani (Universitas Pakuan, 2023)
ABSTRACTThe research aims to examine the influence of the role of pattern or style on leadership, organizational culture, and motivation on the performance of the Indonesian Navy's West Provision Center Depot personnel. Data collection used a questionnaire, and data analysis used structural equation modelling (SEM). This study concludes that organizational culture easily influences personnel performance because each person has a good character already formed since the first time they enter the Dopusbekbar environment. Likewise, motivation is shown by a mental attitude when doing a job according to responsibility. Conversely, the command system factor contributes to the low influence of leadership style on personnel performance. The managerial implications that need to be carried out include, among other things, that each officer is responsible for the formation of organizational culture and motivation of personnel trying to improve performance through increased competence and other psychological skills both formally and informally.ABSTRAKPenelitian bertujuan mengkaji pengaruh peran pola atau gaya pada kepemimpinan, budaya organisasi, dan motivasi terhadap kinerja personil Depo Pusat Pembekalan Barat TNI AL. Pengumpulan data menggunakan kuesioner dan analisis data menggunakan structural equation modeling (SEM). Studi ini menyimpulkan bahwa budaya organisasi mudah mempengaruhi kinerja personil karena pada setiap personil sudah dibentuk karakter dengan baik sejak pertama kali masuk di lingkungan Dopusbekbar. Begitu juga, motivasi ditunjukkan oleh sikap mental pada setiap melakukan suatu pekerjaan sesuai dengan tanggung jawab. Sebaliknya, faktor sistem komando berkontribusi pada rendahnya pengaruh gaya kepemimpinan terhadap kinerja personil. Implikasi manajerial yang perlu dilakukan antara lain, setiap perwira bertanggung jawab dalam pembentukan budaya organisasi dan motivasi personil berusaha meningkatkan kinerja melalui peningkatan kompetensi dan keahlian lain secara psikologis baik secara formal maupun informal.